The Origins of War in Mozambique A History of Unity and Division - Funada-Classen, Sayaka (African Minds, 2013)
The independence of Mozambique in 1975 and its decolonisation process attracted worldwide attention as a successful example of national unity. Yet, the armed conflict that broke out between the government and the guerrilla force in 1977 lasted for sixteen years and resulted in over a million deaths and several million refugees, placing this concept of national unity into doubt. For nearly twenty years, Sayaka Funada-Classen interviewed people in rural communities in Mozambique. By examining their testimonies, historical documents, previous studies, international and regional politics, and the changes that various interventions under colonialism brought to the traditional social structure, this book demonstrates that the seeds of division had already been planted while the liberation movement was seeking unity in the struggle years. Presenting a comprehensive history of contemporary Mozambique, this book is indispensable for Mozambican scholars. It promises to serve as a landmark study not only for historians and the scholars of African studies but also for those who give serious consideration to the problems of conflict and peace in the world.